1905 N.C. Sess. Laws 488 - (:unkn) unknown (My University, 1905)
Priv. Laws, ch. 174, § 60: That the board of commissioners of said town shall have power to pass ordinances for the protection of the persons and property of the citizens of the same, and to that end may pass an ordinance making it unlawful to discharge any gun, pistol, or other fire-arm within the corporate limits of the said town or within one-fourth of a mile from the corporate limits of the same, as set out in section two of this act, and any person found guilty of violating the provisions of this section may be punished in the same manner as if the offense had been committed within the corporate limits as aforesaid.
Keywords: DISCHARGE